In Vivo Antimalarial Activity of Leaf Latex of Aloe melanacantha against Plasmodium berghei Infected Mice. (21st June 2021) - Gebremariam, Gebrehiwot Kiros; Desta, Haile Kassahun; Teklehaimanot, Tekleab Teka; Girmay, Tsgab Gebrecherkos
Abstract : Background . Malaria is a major health concern in the world in general and developing countries in particular. Nowadays, the control of malaria has ended up steadily more complex due to the spread of drug-resistant parasites. Medicinal plants are the verifiable source of compelling antimalarial drugs. The present study was aimed to assess the in vivo antimalarial activity of leaf latex of A. melanacantha against Plasmodium berghei in mice. Methods . Acute oral toxicity study of the leaf latex was assessed in mice up to a dose of 2, 000 mg/kg. A four-day suppressive model was utilized to investigate the antimalarial activity of the plant. Three extract doses, 100, 200, and 400 mg/kg/day, doses of the plant leaf latex, chloroquine, 10 mg/kg (positive control) and distilled water, and 10 mL/kg (negative control) were administered to mice. Percent parasitemia suppression, packed cell volume, mean survival time, body weight, and rectal body temperature were used to determine antimalarial activity. Results . Test groups treated with 100, 200, and 400 mg/kg of the latex showed a significant parasitemia suppression in dose dependent manner compared to the negative control with an IC50 of 22.63 mg/ml. Mice treated with 100, 200, and 400 mg/kg have shown parasitemia suppression of 14.86%, 29%, and 43.2%, respectively. The chemosuppression was significant (P < 0.05 ) at all doses compared to the negative control. Similarly, mice treated with 100 mg/kg, 200 mg/kg, and 400 mg/kg have shown a significant survival time compared to the negative control. At the same time, weight loss reduction was observed within the test groups treated with 100 mg/kg and 200 mg/kg of the latex while the test groups treated with 400 mg/kg had showed almost no weight loss reduction. The latex also reversed the PCV reduction significantly (P < 0.05 ) at 200 mg/kg and 400 mg/kg doses and prevented rectal temperature dropping significantly (P < 0.05 ) at all doses. Conclusion . The leaf latex of A. melanacantha has shown significant antimalarial activity against P. berghei in mice supporting the genuine traditional antimalarial usage of the plant.